PENYEDIAAN AIR BERSIH DENGAN MENGIMPLEMENTASIKAN KATUP TEKAN POMPA HYDRAM MODEL BOLA DI DUSUN PANGKUNG - M. Suarda; A.A.A. Suryawan; I G.N.O. Suputra (Buletin Udayana Mengabdi, 2016)
Community of Pangkung sub-village of Belantih village in Bangli district very hard to access clean water. Inadition, Belantih-Kintamani Public Health Center located in the region. To meet the needs of clean water canbe overcome by utilizing the potential of existing water sources, one of which is Pangkung spring. Thesprings elevation is lower 125 meters from health centers and residential population, so it requires a tool suchas a pump to raise the water. In order to reduce operating costs then used hydram pump. Based on the resultsof studies in which the new spherical shaped hydram pump delivery valve model gives better efficiency thanthe plate model, then the hydraulic ram is made and mounted using the spherical shaped model. Consideringthat Pangkung spring discharge is only 3 liters/sec then clean water to meet the needs of the community andthe health center that will be used hydram pump which is expected to produce about 0.2 liters/sec. Whilewastewater from hydraulic ram will be streamed using the gasoline engine-driven pump to meet the needs ofthe people in the Pangkung sub-village of Belantih village of about 1 liter/sec. Hydram pump that has beenmade and installed has been able to operate properly. The results of measurements at the peak of the dryseason in September produce the pumping capacity of 0.17 liters/sec with 3 liters/sec of the drive watercapacity.